Membrane potential imaging in the nervous system methods and applications - Canepari, Marco; Zecevic, Dejan (Springer, 2011)
Membrane Potential Imaging in the Nervous System: Methods and Applications describes optical techniques to monitor neuronal membrane potential signals. The knowledge upon which voltage-imaging technique is based was generated over several decades and the aim of this book is to provide a single comprehensive source of information on different types of voltage-imaging techniques, including overviews, methodological details, examples of experimental measurements, and future developments. The book is structured in five sections, each containing several chapters written by experts and major contributors to particular topics. The volume starts with a historical perspective and fundamental principles of membrane potential imaging and continues to cover the measurement of membrane potential signals from dendrites and axons of individual neurons, measurements of the activity of many neurons with single cell resolution, monitoring of population signals from the nervous system, and concludes with the overview of new approaches to voltage-imaging. Membrane Potential Imaging in the Nervous System is targeted at all scientists interested in this mature but also rapidly expanding imaging approach.